(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The integration of Information and Communication Technology (ICT) with multimedia resources has emerged as a transformative force in language education, particularly in developing academic and professional writing proficiency among engineering students. Traditional methods of teaching writing often emphasize structure and grammar but fall short in engaging learners or catering to diverse learning needs. This study explores the pedagogical potential of ICT-driven tools such as Grammarly, Write & Improve, Turnitin feedback, and multimedia platforms including videos, interactive modules, and digital storytelling to foster writing competence in undergraduate engineering classrooms. By adopting an application-oriented approach, the research highlights how these technologies provide immediate feedback, encourage self-directed learning, and promote creativity in writing tasks. The methodology employs a quasi-experimental design with pre- and post-test assessments conducted on two groups: one exposed to conventional instruction and the other integrated with ICT and multimedia resources. Quantitative results from writing assessments are complemented by qualitative data drawn from learner reflections and instructor observations. Findings reveal significant improvement in vocabulary usage, grammatical accuracy, coherence, and overall confidence in the experimental group, demonstrating the effectiveness of ICT-based interventions. Moreover, the study emphasizes that multimedia integration not only enriches the writing process but also nurtures critical thinking and professional communication skills essential for engineering graduates. This article argues that ICT-driven writing pedagogy represents more than a supplementary aid; it is a paradigm shift that aligns with global trends in digital literacy and the requirements of the 21st-century workplace. The study concludes by recommending structured integration of ICT and multimedia into the engineering curriculum, ensuring that students are better prepared to meet academic challenges and professional communication demands in an increasingly digitalized world.